Effect of CETP inhibition with evacetrapib in patients with diabetes mellitus enrolled in the ACCELERATE trial. Issue 1 (15th March 2020) - Menon, Venu; Kumar, Anirudh; Patel, Divyang R; St John, Julie; Riesmeyer, Jeffrey; Weerakkody, Govinda; Ruotolo, Giacomo; Wolski, Kathy E; McErlean, Ellen; Cremer, Paul C; Nicholls, Stephen J; Lincoff, A Michael; et al.
Abstract : Background: High-density lipoprotein (HDL) levels are inversely associated with cardiovascular risk. Cholesteryl ester transfer protein inhibition with evacetrapib results in a marked increase in HDL and reduction in low-density lipoprotein (LDL) levels. We evaluated the impact of treatment with evacetrapib versus placebo in the subset of 8236 patients with diabetes mellitus (DM) enrolled in the Assessment of Clinical Effects of Cholesteryl Ester Transfer Protein Inhibition with Evacetrapib in Patients at a High Risk for Vascular Outcomes trial. Methods and results: Time to first occurrence of any component of the primary composite endpoint of cardiovascular death, myocardial infarction, stroke, revascularization, and hospitalization for unstable angina was compared among patients with DM randomized to treatment with evacetrapib (n=4127) or placebo (n=4109) over a median of 26 months of follow-up. The mean baseline LDL at initiation was 80 mg/dL with a mean baseline HDL of 44 mg/dL. In patients with DM, evacetrapib resulted in a 131% mean increase in HDL levels and a 32% mean decrease in LDL at 3 months that was sustained during the course of the trial. At 6 months, hemoglobin A1c (HbA1c) levels were lower with evacetrapib than placebo (7.08% vs 7.15%, p=0.023). Composite event rates were higher in patients with DM than without DM (Kaplan-Meier estimates: 15.2% vs 10.6%, HR 1.46, 95% CI 1.30 to 1.64, p<0.001). In the DM group, event rates for the composite endpoint (14.5% evacetrapib vs 16% placebo, HR 0.95, 95% CI 0.85 to 1.07, p=0.38) and individual components of the composite were similar for both evacetrapib and placebo groups. No significant treatment interaction between treatment assignment and diabetes status was noted. Conclusion: Despite a favorable increase in HDL, and decreases in LDL and HbA1c levels in patients with DM, we observed no benefits of treatment with evacetrapib on prespecified clinical outcomes in this high-risk population.